Faktor-Faktor Yang Mempengaruhi Firm Value Sebelum Dan Di Masa Pandemi COVID-19 - Fielbert, Fielbert; Yanti, Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The aim of this study was to determine the influence of the capital structure, liquidity, profitability and size of the company on firm value. The research data that was processed came from the 2019-2020 financial statements of manufacturing companies listed on the IDX. Data samples were taken by purposive sampling which resulted in 56 companies. Data processing, multiple linear regression analysis and different test used the IBM SPSS 25 program. pre-COVID-19 pandemic regression testing results showed that profitability and liquidity affected firm value, while capital structure and firm size do not. The regression test results during the COVID-19 pandemic stated that profitability affects firm value, while capital structure, liquidity and firm size do not. The results of the different tests show that there is no difference between the mean firm value before and during the COVID-19 pandemic.